Chapter 1 Postformalism An Introduction - Stejskal, Jakub (Taylor & Francis, 2023)
This chapter introduces the idea of a postformalist aesthetic theory of reconstructing remote artefacts aesthetic statuses. The case is immune to the misgivings about aesthetic enquiry prevalent in the humanities and social sciences, since it does not assume that recovering such statuses involves experiencing the artefacts potential to provide an intrinsically rewarding gratification of the senses, of the intellect, or of both together. Postformalist aesthetics sees itself as part of a broad investigation into the nature of evaluative attitudes towards visually conspicuous artefacts. Such a broad investigation represents a necessary step towards establishing whether an object was meant to merit aesthetic attention.